2013
DOI: 10.1111/jeb.12285
|View full text |Cite
|
Sign up to set email alerts
|

Socially flexible female choice and premating isolation in field crickets (Teleogryllus spp.)

Abstract: Social influences on mate choice are predicted to influence evolutionary divergence of closely related taxa, because of the key role mate choice plays in reproductive isolation. However, it is unclear whether females choosing between heterospecific and conspecific male signals use previously experienced social information in the same manner or to the same extent that they do when discriminating among conspecific mates only. We tested this using two field cricket sister species (Teleogryllus oceanicus and Teleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 58 publications
(81 reference statements)
3
32
0
Order By: Relevance
“…Another potential explanation is that discriminating between species may be somewhat distinct from within-species mate choice. Consistent with this idea, previous work has found that some mate choice strategies used within species are not applied between species in threespine sticklebacks [43,54] and crickets [75].…”
Section: Discussionmentioning
confidence: 53%
“…Another potential explanation is that discriminating between species may be somewhat distinct from within-species mate choice. Consistent with this idea, previous work has found that some mate choice strategies used within species are not applied between species in threespine sticklebacks [43,54] and crickets [75].…”
Section: Discussionmentioning
confidence: 53%
“…Indeed, adult field crickets show behavioural differences based upon the male calling environments that they experienced recently (Bailey & Macleod, 2014;Bailey & Zuk, 2008, 2009) and as juveniles (Bailey, Gray, & Zuk, 2010;DiRienzo, Pruitt, & Hedrick, 2012;Kasumovic, 2013;Kasumovic, Hall, & Brooks, 2012). Specifically, female field crickets have repeatedly been shown to express stronger responses to male calls following exposure to less variable calls (Kasumovic et al, 2012), less preferred calls (Bailey & Zuk, 2009), or silence (Bailey & Macleod, 2014;Bailey & Zuk, 2008). If our females did remember their social environment more than the 6 days prior to testing, then their behaviour during the test may have been based on more than just the information gathered while in the low-or high-density treatments.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significantly positive relationship between the total number of males that females saw during their penultimate stage and how selective they are as adults (Pearson correlation R 2 =0.0976, N=96, P=0.0019) Rutledge et al 2010). Studies on the effects of the experience with the presence vs absence of experience with male courtship signals in some of these studies are biologically relevant (e.g., Bailey and Zuk 2008;Bailey 2011;Bailey and Macleod 2014). However, future studies on SCAP in all animal taxa should be sure to investigate the variation in the levels of experience (as opposed to presence vs absence), with consideration for the appropriate experimental design (e.g., experience with simultaneous vs subsequent male encounters and/or variation in encounter rate) to manipulate the perceived availability of potential mates.…”
Section: Female Selectivitymentioning
confidence: 92%
“…While the relationship between total males and the likelihood for females to be receptive to males with small tufts is negative, it is not significant (logistic regression Z=1.586, P=0.1130). Vertical lines indicate the standard error of the predicted probability of the logistic regression fit invertebrate species adds to current research that demonstrates that invertebrate behaviors are not rigid in their matingpref- erences (butterflies: Westerman et al 2012pref- erences (butterflies: Westerman et al , 2014 crickets: Bailey and Zuk 2008;Bailey 2011;Kasumovic et al 2012;Bailey and Macleod 2014;Atwell and Wagner 2014; fruit flies: Dukas 2005; katydids: Fowler-Finn and Rodriguez 2012; wolf spiders: Hebets 2003;Hebets and Vink 2007;Hebets 2007; …”
mentioning
confidence: 93%
See 1 more Smart Citation